The use of transbronchial cryobiopsy for diffuse parenchymal lung disease in critically ill patients with acute hypoxemic respiratory failure—A case series. (25th March 2021) - Matta, Atul; Gupta, Ena; Swank, Zulma; Aragaki‐Nakahodo, Alejandro; Cooley, Joseph; Caudell‐Stamper, Danielle N.; Benzaquen, Sadia
Abstract: Objectives: Accurate diagnosis and management of undifferentiated diffuse parenchymal lung disease (DPLD) in critically ill patients is challenging. Transbronchial forceps biopsies have limited utility and surgical lung biopsies can be detrimental for critically ill patients. Transbronchial cryobiopsy (TBC) has shown increased diagnostic yield compared to conventional forceps biopsy in DPLD. However, TBC has not been studied in intensive care unit (ICU) patients. In this case series, we describe our experience with TBC for diagnosis of DPLD in ICU patients with acute hypoxemic respiratory failure. Methods: This case series includes critically ill patients who underwent TBC at two different tertiary care hospitals. Procedures were performed by the same interventional pulmonologist using the two therapeutic bronchoscopes with a 2.8‐mm working channel, and a 1.9‐ or 2.4‐mm cryoprobe. Results: We performed TBC in 17 patients of which 12 (70.1%) were performed at bedside in ICU without fluoroscopic guidance. Pathological diagnosis was made in 15 (88%) patients which resulted in changes in management in most of these patients. Six patients (35.3%) developed pneumothorax post‐procedure with 5 (29.4%) requiring a chest tube. Moderate bleeding was noted in one (6%) patient and no severe or fatal bleeding occurred. Our 30‐day ICU mortality was 47% (n = 8); however, no deaths were directly attributable to the procedure. Conclusions: TBC is a feasible technique with an acceptable complication rate and a fairly high histopathological yield in ICU patients with DPLD and acute hypoxemic respiratory failure. Appropriate diagnosis can be crucial in making management decisions for these patients.